Effectiveness of Yoga Movement Suryanamaskar of Dysmenorrhoea Pain Reduction of Adolescent - Levi Tina Sari (Journal of Ners and Midwifery, 2018)
In adolescence, a physical phenomenon associated with puberty is in biological processes that lead to the ability to reproduce years marked by menstruation, some women must have experienced pain during menstruation in the form of pain. The purpose of this research was to analyze the effectiveness of yoga suryanamaskar movement to decrease dysmenorrhea pain of adolescent girls. This research used pre-post design, with 20 respondents of the 27 total population. The research was measured by pain scale 0-10 with data analysis using paired sample t-test. The results showed that there was an average increase before and after the intervention of 3.5 points. Test results obtained means there was a significant difference between before and after treatment. Yoga suryanamaskar combines motion, breathing and relaxation techniques, which aimed to feel comfortable. Yoga with body suryanamaskar movement re- quired adequate oxygen intake in order to burn glucose into ATP and burn fat in the body, at that time endorphin hormone appears in order to provide pain relief. So it can be recommended to adolescents as training to reduce dysmenorrhea disk.